Schizophrenia Patients With Prevotella-Enterotype Have a Higher Risk of Obesity - Liang, Ying; Shen, Yang; Li, Gaofei; Yuan, Ye; Zhang, Meng; Gao, Jiayu (Frontiers in Psychiatry, 2022)
Recent studies have indicated the critical influence of gut microbiota on the occurrence of obesity. There is a significant risk of obesity in people with schizophrenia. This work proposed that the disorder of gut microbiota in patients with schizophrenia was based on microbial enterotypes. Ninety-seven patients with schizophrenia and 69 matched health controls were eligible. The fresh feces of all the subjects were collected and used to complete 16S rRNA sequence. Statistical analysis was performed to identify the intestinal type of gut microbiota and analyze their potential effects on metabolic function. The patients with enterotype-P had a higher BMI than that of the others. Several differences in the gut microbes of enterotype-P were found between the patients and the controls. Proteobacteria and Firmicutes had significantly higher abundance in the patients’ group with enterotype-P. The Bacteroidetes had higher abundance in health controls with enterotype-P. Different metabolic pathways of the microbiota with the enterotype-P were identified in the subjects categorized in different BMI intervals. The schizophrenia patients had a significantly higher BMI than that of health controls. The patients with enterotype-P had a higher BMI. Therefore, the enterotype-P might have a critical influence on a variety of metabolic pathways to disturb the metabolism of glucose and lipid in human body.